Comparative analysis of MTP -493G/T and ABCG2 34G/A polymorphisms and theirs expression in HIV-associated lipodystrophy patients - Singh, HariOm; Jori, Chandrashekhar; Shyamveer; Mahajan, Supriya D.; Aalinkeel, Ravikumar; Kaliyappan, Kathiravan; Schwartz, Stanley A.; Bhattacharya, Meenakshi; Shaikh, Ruhi; Salve, Madhukar; Deshmukh, Jyoti; Ali, Nemat; et al. (Frontiers in Cardiovascular Medicine, 2023)
HIV-associated lipodystrophy (HIVLD) is a metabolic condition with an irregularity in the production of lipoprotein particles and its occurrence varies among HIV-infected patients. MTP and ABCG2 genes have a role in transport of lipoproteins. The polymorphisms of MTP -493G/T and ABCG2 34G/A affect its expression and influence the secretion and transportation of lipoproteins. Hence, we investigated the MTP -493G/T and ABCG2 34G/A polymorphisms in 187 HIV-infected patients (64 with HIVLD and 123 without HIVLD) along with 139 healthy controls using PCR-RFLP and expression analysis using Real-time PCR. ABCG2 34A allele showed an insignificantly reduced risk of LDHIV severity (P=0.07, OR=0.55). MTP -493T allele exhibited a non-significantly reduced risk for the development of dyslipidemia (P=0.08, OR=0.71). In patients with HIVLD, the ABCG2 34GA genotype was linked with impaired LDL levels and showed a reduced risk for LDHIV severity (P=0.04, OR=0.17). In patients without HIVLD, the ABCG2 34GA genotype was associated with impaired triglyceride levels with marginal significance and showed an increased risk for the development of dyslipidemia (P=0.07, OR=2.76). The expression level of MTP gene was 1.22-fold decreased in patients without HIVLD compared with HIVLD patients. ABCG2 gene was upregulated 2.16-fold in patients with HIVLD than without HIVLD. In conclusion, MTP -493C/T polymorphism influences the expression level of MTP in patients without HIVLD. Individuals without HIVLD having ABCG2 34GA genotype with impaired triglyceride levels may facilitate dyslipidemia risk.